Modifying DSSAT crop models for low-input agricultural systems using a soil organic matter-residue module from Century - Gijsman, A.J.; Hoogenboom, Gerrit; Parton, WJ; Kerridge, Peter C. (Wiley, 2002)
In low-input systems, where most nutrients become available from soil organic matter (SOM) and residue turnover, the applicability of DSSAT (Decision Support System for Agrotechnology Transfer) crop simulation models is limited because (i) it recognizes only one type of SOM (i.e., humus) and recently added, but not yet humified, residue; (ii) it does not recognize a residue layer on top of the soil; (iii) newly formed humus is given a fixed C/N ratio of 10; (iv) only one litter pool is recognized for N although three are recognized for C; (v) for residues with C/N ratios <25, the three litter pools for C decompose at a rate that is independent of the residue's N concentration; and (vi) SOM and residue flows are independent of soil texture. A SOM residue module from the CENTURY model was incorporated in the DSSAT crop simulation models, and a residue layer was added on top of the soil. Modifications were also made in the senescence module of CROPGRO, a model within DSSAT, so that senesced material is now added daily to the soil. Evaluation of the model, using a data set of 40 yr of bare fallow, showed an excellent fit [product moment correlation coefficient (r) of 0.983] between simulated and measured values for SOM-C. Soil N from decomposing SOM and residues was evaluated with data from a Brazilian experiment with seven leguminous residue types. By incorporating the CENTURY SOM residue module, DSSAT crop simulation models have become more suitable for simulating low-input systems and conducting long-term sustainability analyses.